Nitrogen and phosphorus double-doped magnetic hydrothermal carbon as well as preparation method and application thereof

Through the preparation of nitrogen-phosphorus double-doped magnetic hydrothermal carbon, hydrothermal method and co-precipitation technology are used to solve the shortcomings of traditional biochar adsorption performance and recycling, and achieve efficient, low-cost and environmentally friendly dye pollution treatment.

CN119346069APending Publication Date: 2025-01-24ANHUI AGRICULTURAL UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411907728.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing biochar has shortcomings in adsorption performance and recycling, and the traditional pyrolysis method has high energy consumption and carbon emissions, making it difficult to meet the needs of low-carbon and environmental protection.

Method used

The nitrogen -phosphorus dual -doped magnetic water heating charcoal is used to combine the aquatic biomass and nitrogen phosphorus compounds through the water heat method, and prepare high -efficiency adsorption materials through the co -sedimentation technology loading four iron oxidation.

Benefits of technology

The adsorption performance is significantly improved, the maximum adsorption capacity reaches 2430.235mg/g, and the material is easy to recycle and reuse, reducing energy consumption and carbon emissions, and conforming to the concept of low-carbon environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346069A_ABST
    Figure CN119346069A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of nitrogen and phosphorus double-doped magnetic hydrothermal carbon, which comprises the following steps: drying an aquatic biomass precursor, crushing to obtain biomass powder, cleaning the powder, and drying to be absolutely dry; the preparation method comprises the following steps: mixing biomass powder, a nitrogen-phosphorus compound and water, carrying out hydrothermal treatment, cleaning and drying to obtain a hydrothermal carbon precursor; mixing the hydrothermal carbon precursor with a solution containing ferrous iron and ferric iron, and magnetically stirring; in the stirring process, the time and the temperature are controlled; after stirring is completed, adjusting the pH value with an alkaline compound to obtain hydrothermal carbon; the hydrothermal carbon is washed to be neutral and then dried to be absolutely dry, and the nitrogen and phosphorus double-doped magnetic hydrothermal carbon needed by the target is obtained. The invention also provides the nitrogen and phosphorus double-doped magnetic hydrothermal carbon prepared by the method and application of the hydrothermal carbon as a dye adsorbent material. The prepared hydrothermal carbon has the advantages of being good in adsorption performance, convenient to recycle, low in carbon, environmentally friendly, low in cost and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biosorption, and in particular to a nitrogen-phosphorus dual-doped magnetic hydrothermal carbon and a preparation method and application thereof. Background Art

[0002] Dye pollutants, such as methylene blue, are the main source of soil and water pollution. However, in the textile dyeing process, wastewater is inevitably discharged into the environment. Direct discharge of untreated wastewater will pose a serious threat to aquatic ecosystems, soil environment and human health.

[0003] Among the current wastewater treatment technologies, adsorption stands out among all the removal methods due to its simple operation and high removal efficiency. However, as a traditional adsorption material, biochar still has many limitations: single-element doped biochar lacks surface active sites and has poor adsorption performance; the activation method is costly and consumes a lot of resources, which is contrary to the low-carbon and environmental protection concept; carbon materials are difficult to recycle after input, which may cause secondary pollution.

[0004] In view of the above problems, the present invention innovatively proposes a low-carbon and environmentally friendly multi-element doped magnetic hydrothermal charcoal, which significantly improves the adsorption performance of biochar and is easy to recycle and reuse. At the same time, compared with the traditional biochar pyrolysis method, the hydrothermal method of the present invention reduces energy consumption and carbon emissions, providing a low-cost and high-efficiency solution for the treatment of dye pollution. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a nitrogen-phosphorus dual-doped magnetic hydrothermal carbon with good adsorption performance, easy recycling, low carbon and environmental protection, and low cost, as well as a preparation method and application thereof.

[0006] The present invention adopts the following technical solutions to solve the above technical problems: A nitrogen-phosphorus dual-doped magnetic hydrothermal carbon comprises the following steps: (1) Preprocessing The aquatic biomass precursor, lotus stem, is dried and crushed to obtain biomass powder, and the powder is washed and dried to absolute dryness; (2) Hydrothermal The biomass powder, nitrogen and phosphorus compounds and water are mixed, and hydrothermally treated at 180-260°C for 12 hours, and then washed and dried to obtain a hydrothermal carbon precursor; (3) Magnetization The hydrothermal carbon precursor is mixed with a solution containing divalent iron and trivalent iron, and stirred magnetically; during the stirring process, the time and temperature are controlled; after the stirring is completed, the pH is adjusted with an alkaline compound to obtain the hydrothermal carbon; (4) Post-processing The hydrothermal carbon is washed to neutrality and then dried to absolute dryness to obtain the desired nitrogen-phosphorus dual-doped magnetic hydrothermal carbon.

[0007] As one of the preferred embodiments of the present invention, in step (1), the biomass powder is washed with water and ethanol in sequence, and then dried at a temperature of 75-85°C after washing.

[0008] As one of the preferred embodiments of the present invention, in step (2), the nitrogen and phosphorus compound is diammonium hydrogen phosphate.

[0009] As one of the preferred embodiments of the present invention, in step (3), the solution containing divalent iron ions and trivalent iron ions is a mixed solution of ferrous chloride tetrahydrate and ferric chloride hexahydrate, wherein the mixing ratio of divalent iron ions to trivalent iron ions is 1:2.

[0010] As one of the preferred embodiments of the present invention, in step (3), the magnetic stirring time is 30 min and the stirring temperature is 80-90°C.

[0011] As one of the preferred embodiments of the present invention, in step (3), the pH is adjusted in the range of 10 to 13.

[0012] As one of the preferred embodiments of the present invention, in step (4), water, ethanol and water are used to wash the hydrothermal charcoal in sequence until it becomes neutral, and the charcoal is dried at a temperature of 75-85°C after washing.

[0013] A nitrogen and phosphorus dual-doped magnetic hydrothermal carbon is prepared by adopting the preparation method.

[0014] An application of the nitrogen-phosphorus dual-doped magnetic hydrothermal carbon as a dye adsorbent material, wherein the dye includes but is not limited to methylene blue (MB), methyl orange (MO), and malachite green (MG).

[0015] The present invention adopts an innovative method to jointly hydrothermally treat widely available aquatic biomass precursors with nitrogen and phosphorus-rich compounds, and then uses co-precipitation technology to load ferroferric oxide onto the resulting product, successfully preparing nitrogen and phosphorus dual-doped magnetic hydrothermal carbon materials.

[0016] The advantages of the present invention compared to the prior art are: (1) The present invention realizes nitrogen and phosphorus dual element doping by a one-step method, enriching the number of adsorption sites of hydrothermal carbon, so that it exhibits more excellent adsorption performance when treating wastewater; and when ferroferric oxide is loaded on hydrothermal carbon, its dispersibility and stability are also significantly improved. This is because hydrothermal carbon, as an efficient carrier, can effectively inhibit the agglomeration of ferroferric oxide particles, thereby ensuring that the composite material maintains a high specific surface area (102.4460m 2 / g) and abundant adsorption sites, and the specific surface area is increased by about ten times compared with that before magnetization; at the same time, the loading of ferroferric oxide also provides more active sites for the reaction, significantly improving the adsorption capacity of dyes in wastewater, with the maximum adsorption amount reaching 2430.235 mg / g, which solves the problem of lack of active sites and poor adsorption performance of traditional hydrothermal carbon. (2) The present invention prepares the corresponding biochar based on the hydrothermal method. The water molecules contained in the container during the hydrothermal method are conducive to the formation of fine-structured products with more oxygen-containing functional groups. The traditional pyrolysis method, such as the tubular furnace firing method, is usually carried out at a higher temperature. Although it can obtain products with a higher degree of graphitization and good stability, the material migration and reaction speed at high temperature may be faster, which may lead to the product uniformity not being as good as the hydrothermal method, and the distribution of active sites may also be affected. In essence, the structural composition and adsorption mechanism of the biochar prepared by the hydrothermal method and the pyrolysis method are completely different. The biochar prepared by the pyrolysis method The main components of biochar are all C elements, which have been highly graphitized. However, since the reaction temperature of biochar prepared by hydrothermal method is between 180 and 260°C, its main components are still C, H, and O, and it still contains a large number of oxygen-containing functional groups. These oxygen-containing functional groups are more conducive to the subsequent loading of magnetic particles and the efficient adsorption of pollutants. In addition, compared with the traditional pyrolysis method for preparing biochar, the operation steps of the present invention are simpler, the reaction temperature is lower, and the requirements for reaction equipment are lower, which further enhances its economic feasibility and environmental adaptability, and solves the problems of complex production process and high cost of traditional biochar preparation methods.

[0017] (3) The present invention cleverly selects lotus stems, which are widely available agricultural and forestry waste, as the core raw material. This innovative measure not only effectively addresses the problem of unnecessary waste of resources and ecological environmental pollution caused by the natural decay of lotus stems, but also demonstrates a high degree of resource conservation and environmental friendliness through the recycling of raw materials. In addition, lotus stems are a perennial aquatic plant that is rich in a large amount of nitrogen sources and can also play a role of self-doping in the hydrothermal process. The present invention continues to exert its excellent adsorption performance in multiple treatment cycles. After five adsorption and desorption cycles, the adsorption amount is 70% of the initial value, which significantly reduces the material cost of each treatment process.

[0018] (4) The magnetic hydrothermal carbon material prepared by the present invention exhibits excellent magnetic response performance, which not only realizes the easy separation and efficient recovery of the material, but also promotes the possibility of reuse; by applying an external magnetic field, the magnetic hydrothermal carbon can quickly aggregate and form magnetic chains, thereby being more conveniently separated from the wastewater. Compared with traditional filtration or centrifugation steps, it is simpler and faster, and also greatly improves the separation speed and efficiency, providing great convenience for the separation, recovery and reuse of the material. This efficient magnetic separation technology also lays a solid foundation for the reuse of the material; this series of advantages together constitute a closed-loop green preparation system, which solves the problem of secondary pollution to the environment caused by the difficulty of separation and recovery after traditional biochar adsorption.

[0019] (5) The present invention uses diammonium hydrogen phosphate as a dopant to achieve simultaneous doping of nitrogen and phosphorus elements, significantly simplifying the doping process, improving the doping efficiency, and ensuring the uniformity of the doping process. In addition, the structural stability and chemical stability of biochar are significantly enhanced through dual doping of nitrogen and phosphorus and loading of magnetic particles.

[0020] (6) The present invention combines lotus stems with diammonium hydrogen phosphate for hydrothermal treatment, which not only achieves multi-element doping and provides more adsorption sites, thereby significantly improving the adsorption performance; at the same time, the hydrothermal method also introduces more oxygen-containing functional groups. These oxygen-containing functional groups can serve as active sites to additionally load magnetic particles, which improve the adsorption performance. The combination of the two has an effect of one plus one being greater than two (doping and magnetization synergistic effect). BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is the specific surface area analysis result of the biochar of the present invention and comparative example 1; Figure 2 It is the X-ray spectrum test result of the nitrogen-phosphorus dual-doped magnetic hydrothermal carbon of the present invention (in the figure, figure a is the X-ray spectrum diagram; b is the C element distribution diagram; c is the N element distribution diagram; d is the O element distribution diagram; e is the P element distribution diagram; f is the Fe element distribution diagram); Figure 3 It is the XRD test results of the biochar of the present invention and comparative examples 1 to 3 (in the figure, figure a is the result of Example 2 and pure water hydrothermal biochar; figure b is the result of the biochar of comparative examples 1 to 3); Figure 4 The scanning electron microscope images of the nitrogen and phosphorus dual-doped magnetic hydrothermal carbon of the present invention before and after adsorption (different magnifications); Figure 5 It is the adsorption condition of the nitrogen and phosphorus dual-doped magnetic hydrothermal carbon of the present invention at different temperatures and different concentrations (the results of fitting by Langmuir and Freundlich models respectively); Figure 6These are the adsorption results of nitrogen and phosphorus doped magnetic hydrothermal carbon at different times and initial concentrations; Figure 7 It is the change of adsorption amount and removal rate of the nitrogen and phosphorus dual-doped magnetic hydrothermal carbon under different cycle times of the present invention. DETAILED DESCRIPTION

[0022] The embodiments of the present invention are described in detail below. The embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following embodiments. At the same time, the raw materials, reagents, and devices used in the following embodiments, unless otherwise specified, can be obtained from conventional commercial channels, or can be obtained by existing methods; unless otherwise specified, the methods used in the embodiments of the present invention are methods mastered by those skilled in the art.

[0023] Example 1 The preparation method of the nitrogen and phosphorus dual-doped magnetic hydrothermal carbon in this embodiment is as follows: (1) Preprocessing The lotus stems are dried, crushed and sieved through a 100-mesh sieve to obtain lotus stem powder; the lotus stem powder is washed with water and ethanol in turn, and then placed in an oven at 75° C. to dryness for later use.

[0024] (2) Hydrothermal Take 2g lotus stem powder, add 2g diammonium hydrogen phosphate and 60ml deionized water, stir magnetically for 2h, then move into a hydrothermal reactor and carry out hydrothermal reaction at 180℃ for 12h; after the reaction is completed, take it out, wash it with water and ethanol in turn, and bake it in a 75℃ oven until it is absolutely dry to obtain a hydrothermal carbon precursor.

[0025] (3) Magnetization Take 1g of hydrothermal carbon precursor, add 0.77g of ferrous chloride tetrahydrate, 2.10g of ferric chloride hexahydrate, and 50ml of deionized water, and stir magnetically at 80°C for 30min; after stirring, take out and adjust the pH to 10 with 10mol / L sodium hydroxide solution to obtain hydrothermal carbon.

[0026] (4) Post-processing The hydrothermal carbon was washed with water, ethanol and water in sequence until it was neutral, and then placed in a 75°C oven to dry, thereby obtaining the desired nitrogen-phosphorus dual-doped magnetic hydrothermal carbon.

[0027] Example 2 The preparation method of the nitrogen and phosphorus dual-doped magnetic hydrothermal carbon in this embodiment is as follows: (1) Preprocessing The lotus stems are dried, crushed and sieved through a 100-mesh sieve to obtain lotus stem powder; the lotus stem powder is washed with water and ethanol in turn, and then placed in an oven at 80° C. to dryness for later use.

[0028] (2) Hydrothermal Take 2g lotus stem powder, add 2g diammonium hydrogen phosphate and 60ml deionized water, stir magnetically for 2h, then move into a hydrothermal reactor and carry out hydrothermal reaction at 220℃ for 12h; after the reaction is completed, take it out, wash it with water and ethanol in turn, and bake it in an oven at 80℃ until it is absolutely dry to obtain a hydrothermal carbon precursor.

[0029] (3) Magnetization Take 1g of hydrothermal carbon precursor, add 0.77g of ferrous chloride tetrahydrate, 2.10g of ferric chloride hexahydrate, and 50ml of deionized water, and stir magnetically at 85°C for 30min; after stirring, take out and adjust the pH to 11 with 10mol / L sodium hydroxide solution to obtain hydrothermal carbon.

[0030] (4) Post-processing The hydrothermal carbon was washed with water, ethanol and water in sequence until it was neutral, and then placed in an oven at 80°C to dryness to obtain the desired nitrogen-phosphorus dual-doped magnetic hydrothermal carbon.

[0031] Example 3 The preparation method of the nitrogen and phosphorus dual-doped magnetic hydrothermal carbon in this embodiment is as follows: (1) Preprocessing The lotus stems are dried, crushed and sieved through a 100-mesh sieve to obtain lotus stem powder; the lotus stem powder is washed with water and ethanol in turn, and then placed in an oven at 85° C. to dryness for later use.

[0032] (2) Hydrothermal Take 2g lotus stem powder, add 2g diammonium hydrogen phosphate and 60ml deionized water, stir magnetically for 2h, then move into a hydrothermal reactor and perform hydrothermal reaction at 260℃ for 12h; after the reaction is completed, take it out, wash it with water and ethanol in turn, and bake it in an oven at 85℃ until it is absolutely dry to obtain a hydrothermal carbon precursor.

[0033] (3) Magnetization Take 1g of hydrothermal carbon precursor, add 0.77g of ferrous chloride tetrahydrate, 2.10g of ferric chloride hexahydrate, and 50ml of deionized water, and stir magnetically at 90°C for 30min; after stirring, take out and adjust the pH to 13 with 10mol / L sodium hydroxide solution to obtain hydrothermal carbon.

[0034] (4) Post-processing The hydrothermal carbon was washed with water, ethanol and water in sequence until it was neutral, and then placed in an oven at 85°C until it was absolutely dry to obtain the desired nitrogen-phosphorus dual-doped magnetic hydrothermal carbon.

[0035] Example 4 The preparation method of the nitrogen and phosphorus dual-doped magnetic hydrothermal carbon in this embodiment is basically the same as that in Example 2, with the main difference being that in step (2), the hydrothermal reaction is performed at 260° C. for 12 h.

[0036] Example 5 The preparation method of the nitrogen and phosphorus dual-doped magnetic hydrothermal carbon in this embodiment is basically the same as that in Example 2, with the main difference being that in step (2), the hydrothermal reaction is performed at 180° C. for 12 h.

[0037] Example 6 The preparation method of the nitrogen-phosphorus dual-doped magnetic hydrothermal carbon of this embodiment is basically the same as that of Embodiment 2, except that in step (2), 2 g of lotus stem powder is added with 1 g of diammonium hydrogen phosphate and 60 ml of deionized water.

[0038] Example 7 The preparation method of the nitrogen-phosphorus dual-doped magnetic hydrothermal carbon of this embodiment is basically the same as that of Embodiment 2, except that in step (2), 2 g of lotus stem powder is added with 4 g of diammonium hydrogen phosphate and 60 ml of deionized water.

[0039] Example 8 The preparation method of the nitrogen-phosphorus dual-doped magnetic hydrothermal carbon of this embodiment is basically the same as that of Example 2, except that in step (2), 2 g of lotus stem powder is added with 4 g of diammonium hydrogen phosphate and 60 ml of deionized water, and the mixture is stirred magnetically for 2 h and then transferred into a hydrothermal reactor for hydrothermal reaction at 260° C. for 12 h.

[0040] Comparative Example 1 The preparation method of the biochar in this comparative example is basically the same as that of Example 2, with the main difference being that no magnetization and post-magnetization treatment are performed.

[0041] Comparative Example 2 The preparation method of the biochar in this comparative example is basically the same as that of Example 2, with the main difference being that the diammonium hydrogen phosphate in step (2) is replaced by "urea".

[0042] Comparative Example 3 The preparation method of the biochar in this comparative example is basically the same as that of Example 2, with the main difference being that diammonium hydrogen phosphate in step (2) is replaced by "phosphoric acid".

[0043] Experimental Example 1 This experimental example is used to analyze and compare the structural characteristics of the biochar of the present invention and comparative examples 1 to 3.

[0044] The specific surface area analysis, X-ray energy spectrum test, XRD test, scanning electron microscope analysis, etc. were performed on the biochar of the present invention (taking Example 2 as an example) and comparative examples 1 to 3 respectively.

[0045] Figure 1 The specific surface area analysis results of the biochar of the present invention and comparative example 1 are shown in FIG. Figure 1It can be seen that the specific surface area of ​​the biochar after magnetization (the present invention) is 102.4460 m² / g, which is about ten times that of the biochar without magnetization (Comparative Example 1, 11.3021 m² / g), indicating that the "magnetization treatment" can increase the specific surface area of ​​the sample, thereby increasing the contact area between the sample and the dye molecules during the adsorption process. In addition, the pore volume (0.251969 cm³ / g) of the biochar after magnetization (the present invention) is also much higher than that of the biochar without magnetization (Comparative Example 1, 0.047821 cm³ / g), indicating that the number of pores on the surface of the sample increases after the "magnetization treatment", thereby enhancing the pore filling effect and increasing the adsorption amount.

[0046] Figure 2 This is the X-ray spectrum test of the nitrogen and phosphorus doped magnetic hydrothermal carbon of the present invention. It shows that N and P are successfully doped, and ferroferric oxide is also successfully attached to the sample surface, and each element is evenly distributed on the sample surface. In addition, the Fe element is more than the N and P elements, and the magnetized sample has a strong magnetism.

[0047] Figure 3 The XRD test results of the biochar of the present invention and comparative examples 1 to 3 are shown in FIG. Figure 3 It can be seen that compared with pure water hydrothermal (without any element doping, no magnetization, only mixed with pure water for hydrothermal), the doping of impurity elements will destroy the crystalline structure of the hydrothermal carbon, increase its defects and reduce its crystallinity; compared with phosphorus doping (Comparative Example 3), nitrogen doping (Comparative Example 2) destroys the crystalline structure of the biochar more, because the addition of phosphoric acid mainly plays the role of activation and pore formation, while the addition of urea will form nitrogen-containing functional groups, thereby increasing the number of defects; in addition, the diffraction peak of ferrosoferric oxide appears in the XRD diagram of the biochar after magnetization (the present invention), further indicating that the magnetization is successful.

[0048] Figure 4 The scanning electron microscope images of the present invention before and after adsorption are shown in FIG. Figure 4 It can be seen that before adsorption, the surface structure of the hydrothermal carbon shrinks due to the decomposition and reorganization of biomass macromolecules during the hydrothermal process, resulting in uneven shrinkage; at the same time, a large number of ferroferric oxide microspheres appear on the surface, providing a large number of adsorption sites. After adsorption, it can be seen from the corresponding images that a large number of MB molecules are attached to the surface of the sample in an aggregated appearance, and a large number of MB molecules are also attached to the inside of the pores, indicating that pore filling plays an important role in the adsorption process, and the MB molecules on the surface may be attracted to the surface of the magnetic biochar in large quantities due to electrostatic interactions and do not fall off.

[0049] Experimental Example 2 This experimental example is used to test the performance of the nitrogen-phosphorus dual-doped magnetic hydrothermal carbon of the present invention.

[0050] 1. Equilibrium adsorption test at different temperatures and concentrations At 25, 30, and 35° C., 10 mg of the nitrogen-phosphorus dual-doped magnetic hydrothermal carbon prepared in the present invention (using Example 2 as an example) was added to 100 ml of a methylene blue solution (MB) with a concentration of 50-1000 mg / L. After adsorption equilibrium was reached, the solution was taken out and filtered for testing.

[0051] Figure 5 The adsorption performance results of the nitrogen-phosphorus dual-doped magnetic hydrothermal carbon of the present invention at different temperatures and different concentrations. It can be seen that with the increase of the equilibrium concentration of MB, the equilibrium adsorption amount of the hydrothermal carbon to it first increases rapidly, then increases slowly by a small amount, and finally basically reaches stability. At the same time, with the increase of the initial concentration of MB, the adsorption amount of the hydrothermal carbon to it first increases rapidly and then increases slowly until it is basically stable. Figure 5 It can also be seen that the adsorption amount of MB by the hydrothermal carbon prepared by the present invention decreases with increasing temperature, that is, the adsorption amount at 25°C is the largest. This may be because during the adsorption process, the adsorbate (methylene blue) interacts with the surface of the adsorbent (nitrogen-phosphorus doped magnetic hydrothermal carbon). When the temperature is low, the thermal motion of the adsorbate molecules is weak, and the collision probability with the adsorbent surface is relatively low, but as the temperature gradually increases, the molecular thermal motion intensifies, which increases the collision probability with the adsorbent surface, and thus may increase the adsorption amount in the initial stage. However, when the temperature rises to a certain extent, the adsorbate adsorbed on the adsorbent surface begins to gain higher energy, and the desorption process gradually intensifies. As the temperature continues to rise, the difference between desorption and adsorption gradually decreases, and the adsorption amount growth rate gradually decreases macroscopically. When the desorption and adsorption reach equilibrium or even the desorption exceeds the adsorption, the adsorption amount will begin to show a downward trend. In addition, although nitrogen and phosphorus doping may increase the active sites on the adsorbent surface and improve its adsorption performance, the thermal motion of the adsorbate at high temperature may also weaken the interaction between these active sites and the adsorbate, further affecting the adsorption effect. The specific adsorption data are shown in Table 1.

[0052] Table 1 Adsorption performance data at different temperatures and initial concentrations

[0053] 2. Adsorption test at different time and different initial concentration In the adsorption kinetics, 10 mg of the nitrogen-phosphorus dual-doped magnetic hydrothermal carbon of the present invention (Example 2) was added to 100 ml of 50 mg / L, 100 mg / L, 200 mg / L, and 500 mg / L MB solutions at pH = 5 at 25°C, and adsorbed by oscillation at room temperature. Samples were taken and filtered at 0 min, 2 min, 5 min, 8 min, 10 min, 30 min, 60 min, 120 min, and 180 min of adsorption, and the concentration of MB was determined.

[0054] Table 2 shows the adsorption data of nitrogen and phosphorus doped magnetic hydrothermal carbon at different times and different initial concentrations. The corresponding adsorption kinetic results are shown in Figure 6 As shown. Figure 6 It can be seen that the adsorption amount of the nitrogen-phosphorus dual-doped hydrothermal carbon of the present invention increases rapidly within 30 minutes. As the adsorption process proceeds, the adsorption rate gradually decreases and finally reaches an adsorption equilibrium state. This is due to the combined effect of adsorption kinetics and the interaction between the adsorbate and the adsorbent. In the early stage of adsorption, the adsorption rate is fast due to the combined effect of factors such as high adsorbate concentration, many active sites on the surface of the hydrothermal carbon material, and strong interaction between the adsorbate and the carbon material surface; in the middle and late stages of adsorption, due to the combined effect of factors such as reduced active sites, increased diffusion resistance, and weakened interaction between the adsorbate and the carbon material surface, the adsorption rate gradually slows down and finally reaches an equilibrium state.

[0055] The adsorption amount increases with the increase of the initial concentration of MB, reaching the maximum (2430.235 mg / g) when the initial concentration is 500 mg / L. This is because adsorption is divided into physical adsorption and chemical adsorption. When the concentration of MB is high, the effects of physical adsorption and chemical adsorption will be enhanced because more adsorbate molecules have the opportunity to contact and interact with the surface of the hydrothermal carbon material. In particular, chemical adsorption, which usually has higher selectivity and stronger adsorption force, can more effectively capture adsorbate molecules at high concentrations. Therefore, the adsorption amount of hydrothermal carbon will increase with the increase of its concentration.

[0056] Table 2 Adsorption data at different time and different initial concentrations

[0057] III. Removal Rate and Specific Surface Area Tests of Different Examples and Comparative Examples The equilibrium adsorption amount and removal rate of the biochar in Example 2, Examples 4 to 8 and Comparative Examples 1 to 3 were measured respectively.

[0058] When testing the equilibrium adsorption amount, the temperature was set to 25°C, 10 mg of biochar was added to 100 ml, and the initial concentration was 100 mg / L of MB solution. The test results are shown in Table 3. It can be seen from Table 3 that the removal rate of Example 2 is significantly greater than that of other samples. This is because the hydrothermal carbon exhibits the best adsorption performance when the hydrothermal temperature is 220°C. This performance is derived from the co-doping of N and P elements, which changes the surface structure and polarity of the carbon material, thereby improving its adsorption capacity. Double doping may introduce more active sites and functional groups, enhance the interaction with dye molecules, and thus improve the adsorption effect. The magnetization treatment changes the surface properties and separation efficiency of the adsorption material. The magnetization treatment can modify the original hydrothermal carbon by magnetic materials to make it magnetic, so as to facilitate recycling by magnetic separation. In addition, the magnetization treatment may also change the surface structure, composition and polarity of the adsorption material, so that its adsorption performance for dye pollutants changes. At the same time, modifying the active particles to the surface of the biochar after magnetization can also make it carry more positive charges, thereby adsorbing more oxygen-containing anions and improving the adsorption capacity. Therefore, the adsorption performance of Example 2 is significantly higher than that of other examples and comparative examples.

[0059] Table 3 Removal rate measurement results

[0060] The specific surface areas of Example 2 and Comparative Example 1 were measured, and the results are shown in Table 4. It can be seen from Table 4 that the magnetic treatment can improve the specific surface area, active sites and adsorption capacity of the hydrothermal carbon by optimizing the pore structure of the hydrothermal carbon or increasing its surface roughness. At the same time, the magnetic treatment can also improve the dispersibility and stability of the hydrothermal carbon, making it more effective in the adsorption process.

[0061] Table 4 Specific surface area measurement results

[0062] 4. Adsorption and removal rate test under different cycle times The biochar (Example 2 of the present invention) with an initial MB adsorption concentration of 100 mg / L and reaching adsorption equilibrium was immersed in 100 ml of ethanol solution, shaken at a constant temperature of 120 rpm, and washed repeatedly until no blue precipitate was precipitated. The hydrochar was recovered with a strong magnet and dried in an oven at 80°C until it was absolutely dry. The adsorption was repeated at 25°C. After the adsorption equilibrium was reached, the solution was taken out for testing. The test results are shown in Figure 7 shown.

[0063] Depend on Figure 7It can be seen that after the first adsorption-desorption cycle, the adsorption amount of MB by hydrothermal carbon decreased the most. With the increase of the number of cycles, the rate of adsorption decrease gradually slowed down, and the adsorption amount gradually decreased. After five adsorption-desorption cycles, the final adsorption amount was (582.423 mg / g), which was 69.38% of the original adsorption amount (839.376 mg / g), showing excellent cyclic availability.

[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing nitrogen-phosphorus dual-doped magnetic hydrothermal carbon, characterized in that: The steps include: (1) Preprocessing The aquatic biomass precursor, lotus stem, is dried and crushed to obtain biomass powder, and the powder is washed and dried to absolute dryness; (2) Hydrothermal The biomass powder, nitrogen and phosphorus compounds and water are mixed, and hydrothermally treated at 180-260°C for 12 hours, and then washed and dried to obtain a hydrothermal carbon precursor; (3) Magnetization The hydrothermal carbon precursor is mixed with a solution containing divalent iron and trivalent iron, and stirred magnetically; during the stirring process, the time and temperature are controlled; after the stirring is completed, the pH is adjusted with an alkaline compound to obtain the hydrothermal carbon; (4) Post-processing The hydrothermal carbon is washed to neutrality and then dried to absolute dryness to obtain the desired nitrogen-phosphorus dual-doped magnetic hydrothermal carbon.

2. The method for preparing nitrogen-phosphorus dual-doped magnetic hydrothermal carbon according to claim 1, characterized in that: In the step (1), the biomass powder is washed with water and ethanol in sequence, and then dried at a temperature of 75-85°C.

3. The method for preparing nitrogen-phosphorus dual-doped magnetic hydrothermal carbon according to claim 1, characterized in that: In the step (2), the nitrogen and phosphorus compound is diammonium hydrogen phosphate.

4. The method for preparing nitrogen-phosphorus dual-doped magnetic hydrothermal carbon according to claim 1, characterized in that: In the step (3), the solution containing divalent iron ions and trivalent iron ions is a mixed solution of ferrous chloride tetrahydrate and ferric chloride hexahydrate, wherein the mixing ratio of divalent iron ions to trivalent iron ions is 1:

2.

5. The method for preparing nitrogen-phosphorus dual-doped magnetic hydrothermal carbon according to claim 1, characterized in that: In the step (3), the magnetic stirring time is 30 minutes and the stirring temperature is 80-90°C.

6. The method for preparing nitrogen-phosphorus dual-doped magnetic hydrothermal carbon according to claim 1, characterized in that: In the step (3), the pH is adjusted in the range of 10 to 13.

7. The method for preparing nitrogen-phosphorus dual-doped magnetic hydrothermal carbon according to claim 1, characterized in that: In the step (4), water, ethanol and water are used to wash the hydrothermal charcoal in sequence until it becomes neutral, and the charcoal is dried at a temperature of 75-85°C after washing.

8. A nitrogen-phosphorus dual-doped magnetic hydrothermal carbon, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the nitrogen-phosphorus dual-doped magnetic hydrothermal carbon as claimed in claim 8 as a dye adsorbent material.

Citation Information

Patent Citations

  • Method for preparing magnetic biomass charcoal from potamogeton crispus and application thereof

    CN111530419A

  • Junci medulla magnetic powder for dyeing wastewater treatment as well as preparation method and application of same

    CN111871367A

  • Rare earth element-nitrogen and phosphorus co-doped biochar as well as preparation method and application thereof

    CN116492983A